2009
DOI: 10.1097/iop.0b013e3181aa9a73
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Ocular Injury in Visually Asymptomatic Orbital Fractures

Abstract: Visually asymptomatic patients with orbital fractures do not have ocular injury requiring emergent evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 11 publications
1
28
1
1
Order By: Relevance
“…The research by Mellema et al found that asymptomatic patients were unlikely to have severe ocular injury in the setting of an orbital fracture. In addition, visual acuity did not accurately predict the presence of a severe ocular injury [16]. Our findings agree with their statement as 70% of the asymptomatic patients had no neurological findings and 1.0 vision, with the other 30% also having no neurological findings and slightly reduced vision (>0.6).…”
Section: Discussionsupporting
confidence: 72%
“…The research by Mellema et al found that asymptomatic patients were unlikely to have severe ocular injury in the setting of an orbital fracture. In addition, visual acuity did not accurately predict the presence of a severe ocular injury [16]. Our findings agree with their statement as 70% of the asymptomatic patients had no neurological findings and 1.0 vision, with the other 30% also having no neurological findings and slightly reduced vision (>0.6).…”
Section: Discussionsupporting
confidence: 72%
“…Careful evaluation for possible globe rupture must be performed. The majority of pathologies can be present even in visually asymptomatic patients 6. Treatment of any vision-threatening conditions should almost always preclude repair of the fracture until stable.…”
Section: Discussionmentioning
confidence: 99%
“…OPHTHALMOLOGIC EVALUATION Eleven to 15% of orbital fractures are associated with ophthalmological emergencies, the majority of which will present with diminished visual acuity or other visual changes. 8,9 However, it is important to note that although decreased vision in the setting of trauma is common, such a finding is neither 100% sensitive nor specific for ophthalmologic emergencies. For example, testing vision with a near vision card in the absence of reading glasses or with eyelid swelling causing temporary, but significant, astigmatism may result in spuriously poor vision, whereas a self-sealing anterior scleral laceration or a peripheral retinal injury may not significantly alter grossly tested vision.…”
Section: Initial Assessmentmentioning
confidence: 99%